Stock return seasonalities and investor structure: Evidence from China's B-share markets - Martin T. Bohl; Michael Schuppli; Pierre L. Siklos (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
This paper investigates whether seasonalities in daily stock returns are related to the trading behavior of individual and institutional investors. The change in the investor structure of B-share markets in Shanghai and Shenzhen after the abolition of ownership restrictions in 2001 provides a unique testing environment. We show that day-of-the-week effects are attenuated after the market entrance of Chinese individual investors, who had previously not been allowed to trade in B-shares. Our empirical results suggest that institutional rather than individual investors are a main driving force behind such anomalies. In addition, we find evidence of reduced index return autocorrelation and US spillover effects in the post-liberalization period.
URN:NBN:fi:bof-201408072197
Keywords: G12; G14; G18; 330; institutional investors; individual investors; stock return seasonalities; Chinese stock markets; GARCH model